Perineal abscess in pediatrics - Frizzo, Ana Paula Machado; Alves , André Luiz Jardim; Cabral, Kamila Campos; Cascabulho, Ana Maria Esteves; Lima, Fernanda Cardilo; Lessa , Luiza Ramos Kelly; Manhães , Martha Borges Neves; Rodrigues , Wellington Luiz; Gottardi, Lorena de Freitas; Garcia , Paula Martins Ribeiro; Pimentel, Tarcilio Machado (Seven Editora, 2024)
Perineal abscess is a clinical condition that involves the formation of purulent collections in the perineal region, presenting significant debilitating potential due to its high vascularization, which favors the spread of infection and can progress to serious complications such as sepsis and Fournier's syndrome. This article reviews the complexity of the management of perineal abscess in children, highlighting its multifactorial etiology and the need for an individualized approach in diagnosis and treatment, also exposing a case report of perineal abscess in a pediatric patient. The current literature indicates that the appropriate choice of antibiotics, such as ceftriaxone, metronidazole, amoxicillin/clavulanate, and trimethoprim/sulfamethoxazole, is crucial for infection control and prevention of complications, including recurrences and spread of infection. In addition to antibiotic therapy, early surgical drainage is often required for effective management. This study was conducted with a case report on the topic in question, followed up in a pediatric service of a teaching hospital, and through a literature review. To this end, recent scientific articles and theses were used, highlighting the importance of new research to broaden the understanding of the subject and improve clinical results in future cases. DOI:https://doi.org/10.56238/sevened2024.026-053